(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In 2024, Nakkhasen et al. introduced the concept of fuzzy Bd-subalgebras of Bd-algebras. This paper will present the concept of fuzzy dot Bd-subalgebras in Bd-algebras as a generalization of fuzzy Bd-subalgebras. Subsequently, we evaluate the connections of fuzzy dot Bd-subalgebras in the framework of a homomorphism of Bd-algebras. Finally, we propose the concept of strongest fuzzy dot Bd-subalgebras and explain their characteristics in relation to Bd-subalgebras.